Impact of Intellectual Capital and Islamic Corporate Governance on Financial Performance of Indonesian Islamic Commercial Banks - Dahlifah; Putri, Dina Anavia; Mustika, Maya; Tarsono, Ono (SAN Scientific, 2024)
The aim this study is to investigate the relationship between intellectual capital, Islamic commercial banks' financial performance, and Islamic corporate governance in Indonesia from 2017 to 2019. The methodology used in the study is quantitative. The people are all Muslims. Commercial banks that have Financial Services Authority registrations (OJK) over the three-year period (2017-2019). The sample is determined using a saturated sampling technique, resulting in 14 Islamic Commercial Banks and forty-two observations in total. The analytical approach is panel data regression analysis and data processing with Eviews 9. The study's findings demonstrate that intellectual capital has a significant impact on return on assets. In contrast, the Sharia Supervisory Board has little effect on Return on Assets. However, the Commissioners' Board and the Directors Board both significantly influence Return on Assets.